Evaluation of Ship Registry Regulation Provisions on Establishment of a Ship Mortgage - Murat Aydın (İstanbul Hukuk Mecmuası)
This study is based on the provisions of Articles 33-35 of the Ship Registry Regulation (SRR) regarding the establishment of ship mortgages. Accordingly, the scope of application of Art. 33-35 of the SRR was determined in this study. Then, the general principles regarding ship mortgage are emphasised. Finally, within the scope of the establishment of a ship mortgage; the form of the mortgage agreement, the obligation to pay the mortgage fee, the registration request and registration procedure, and the establishment of mortgages on more than one ship or share are analysed. In addition, Article 1014 et seq. of Turkish Commercial Code No. 6102 (TCC) contains provisions on the establishment of ship mortgages. Therefore, in this study, the provisions of the Turkish Commercial Code regarding the establishment of ship mortgages are also emphasised to the extent necessary. On the other hand, the provisions of the Ship Registry Regulation on the establishment of ship mortgages also contain regulations on the practises of the ship registry directorate. Accordingly, while analysing the provisions of Articles 33-35 of the SRR, the practises of the ship registry directorate are also examined in this study.